Kaitan Antara Studi Kelayakan Bisnis Dengan Hukum Ekonomi Syariah - Ade Zuki Damanik (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
A study of business validity can help to understand the legal and regulatory structures that govern the operation of a sharia business, while sharia economic law can provide valuable perspectives on the principles and rules that govern business operations. Understanding the relationship between these two fields can help identify potential challenges and opportunities for sharia, as well as help to identify best practices and case studies that can help Sharia overcome challenges and take advantage of opportunities. This type of research is a descriptive qualitative approach by applying library research methods (library research). The results of the research are used as a determining factor in choosing or rejecting an idea or proposal for a project or undertaking being planned. Meanwhile, Shariah economic law refers to an economic legal system based on Islamic principles and values. In the study of business viability, there are several evaluation factors that need to be considered, such as legality, marketing, and financial aspects. In the context of Shariah economic law, there are several principles that include the Foundations of Mu'awanah, Musyarakah, Manfaah, Antarodhin, Adamul Gharar, Musawah, Ash Shiddiq, Ownership, Governance, and Bir wa Taqwa.